Chromosomal changes in peoples consumed frozen meat in Al- Diwaniyah province - Forat Abd Alhamzah; Dunnia Abdullah Barakat (University of Thi-Qar Journal, 2019)
This study aimed to study chromosomal changes for people who eat frozen meat, the samples were collected from 30 people (males) aged 20-25 years from three different regions, they divided between , the city center and districts and rural areas in addition to control group who were 10 healthy people in the same sex and age and didnt eat frozen meat. Were prepared chromosomes from lymphoid peripheral blood cells, and then calculated changes in the chromosomes . The results of the study showed the presence of abnormalities in the chromosomes of people who lives in city center(third group) as compared to control where it reached 0.13 , but this different was not significant at the level (p <0.01) changes of chromosomal aberration in first and second groups were 0.11 , 0.09 , but did not constitute significant differences. The types of malformations observed in the chromosomes of the study samples included : chromatide breack, chromatide delete , acentric fragmentes showed no numerical changes in the studied groups